TROPHIC INTERACTION BETWEEN BUBO VIRGINIANUS (GMELIN, 1788) (STRIGIFORMES; STRIGIDAE) AND JACANA JACANA (LINNAEUS, 1766) (CHARADRIIFORMES; JACANIDAE) IN THE SOUTHERN PANTANAL OF MATO GROSSO DO SUL (REMUNOM, 2025)
Bubo virginianus (Gmelin, 1788), commonly known as the Great Horned Owl, exhibits a wide distribution throughout the Americas, ranging from northern Canada to southern South America. Despite its extensive range, many aspects of its natural history remain poorly understood, particularly within Brazil and the Neotropical region. Most ecological studies have focused on its feeding habits, revealing a generalist and opportunistic diet dominated by birds and mammals, with variations related to prey availability. During a nocturnal herpetofaunal survey conducted on August 25, 2025, at approximately 23:00 h, in a rural area of Aquidauana, Mato Grosso do Sul, Brazil, we documented a trophic interaction between an adult B. virginianus and a juvenile Jacana jacana (Linnaeus, 1766). The owl was observed perched atop a dead tree holding the prey in its talons before flying away. The event occurred near a wetland area characterized by dense aquatic vegetation, a suitable habitat for J. jacana, which had been previously observed foraging with chicks during daylight hours. Large owls such as B. virginianus have high energetic demands, requiring extensive foraging areas that vary according to prey abundance and habitat structure. In the Pantanal, the diversity of microhabitats and high availability of prey, particularly small mammals and birds, may reduce intraspecific competition and foraging range requirements. This observation represents the first documented record of predation on J. jacana by B. virginianus in the southern Pantanal. Opportunistic records such as this provide valuable contributions to the understanding of predator–prey interactions involving top trophic-level species, complementing indirect dietary studies based on pellet or fecal analyses. The record expands the known prey spectrum of B. virginianus in the Neotropical region, offering new insights into its feeding ecology and the ecological dynamics of wetland environments in the Pantanal biome.